Financial Performance Analysis Of The Balai Yasa Lahat Employees' Cooperative - Leny Veronika; Darwin Kesuma; Mujari Mujari (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
The purpose of this study is analyze the Financial Performance of the Balai Yasa Lahat Employee Cooperative in terms of the Financial Ratios of Liquidity, Solvency, and Profitability. The aim was to determine the financial position of the Balai Yasa Lahat Employee Cooperative. The research method used a quantitative descriptive approach in accordance with the standards of the Regulation of the Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number: 22/PER/M.KUKM/IV/2007 concerning Guidelines for Cooperative Rating. The results of the study show that the analysis of the financial report performance of the Liquidity Ratio at the Balai Yasa Lahat Employee Cooperative from 2021 - 2023 shows a figure with the criteria of "Very Not Ideal" because it is above 200%, in the Current Ratio analysis, namely 307% in 2021, 319% in 2022, and 527% in 2023. The Solvency Ratio analysis shows a figure with the criteria of "Very Not Ideal" because it is below 90% in the Debt Ratio analysis, namely 28% in 2021, 27% in 2022, and 16% in 2023. Meanwhile, in the Debt Equity Ratio (DER) analysis, namely 43% in 2021, 40% in 2022, and 20% in 2023. The Profitability Ratio analysis in the Return On Asset Ratio analysis in 2021 has The ratio is 6.04%, categorized as poor, falling between 4% and 7%. Meanwhile, in 2022 and 2023, the ratios were 2.28% and 2.39%, respectively, categorized as poor, falling below 4%. Meanwhile, in the Return on Equity analysis, the ratio for 2021 was 9.22%, categorized as quite good, falling between 8% and 11%. Meanwhile, in 2022 and 2023, the ratios were 3.26% and 2.96%, respectively, categorized as poor, falling below 4%.